2019
DOI: 10.1002/prep.201800187
|View full text |Cite
|
Sign up to set email alerts
|

Penetration Capability of EFPs Against Explosive Reactive Armor

Abstract: This study aimed to investigate the interference of explosive reactive armor (ERA) on the penetration capability of explosively formed projectiles (EFPs). A numerical simulation model of EFP and the ERA interaction system was established. Flash X‐ray experiments for observing the interaction between EFP and ERA were performed. It turned out that the simulation method and material model was valid. From the numerical simulation, the residual depth of penetration (RDOP) of EFPs with different materials, scales, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Brown et al [3] proposed a successful EFP design scheme under meeting three different goals, and compared experimental results predicted results, and performance goals. With the deepening of the understanding of EFP, it was found that the shape of EFP had a great influence on penetration ability [4][5][6][7]. Targets of different materials and EFPs of different shapes were used as research objects in references [4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown et al [3] proposed a successful EFP design scheme under meeting three different goals, and compared experimental results predicted results, and performance goals. With the deepening of the understanding of EFP, it was found that the shape of EFP had a great influence on penetration ability [4][5][6][7]. Targets of different materials and EFPs of different shapes were used as research objects in references [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of the understanding of EFP, it was found that the shape of EFP had a great influence on penetration ability [4][5][6][7]. Targets of different materials and EFPs of different shapes were used as research objects in references [4][5]. It was studied that adding a reinforcing ring between the shell and the liner can improve the shape, structure, and velocity of the EFP significantly in reference [6].…”
Section: Introductionmentioning
confidence: 99%